Investigation of Solvent Effects on Photophysical Properties of New Aminophthalimide Derivatives-Based on Methanesulfonate - Tan, A.; Bozkurt E.; Kara Y. (Springer New York LLC, 2017)
Novel aminophthalimide derivatives were synthesized starting from (3aR,7aS)-2-(2-hydroxypropyl)-3a,4,7,7a–tetrahydro-1H-isoindole-1,3(2H)-dione (9) , and solvent effects on the photo-physical properties of these newly synthesized aminophthalimide derivatives (compounds 14 and 15) were investigated using UV-Vis absorption spectroscopy, steady-state and time-resolved fluorescence measurements. Both absorption and fluorescence spectra exhibited bathochromic shift with the increased polarity of the solvents for both molecules. Solute-solvent interactions were analyzed using the Lippert-Mataga and Bakhshiev polarity functions, and Kamlet-Taft and Catalan multiple linear regression approaches. The results revealed that these two molecules experienced specific interactions. Furthermore, photo-physical parameters were calculated for both molecules in all of the solvents, such as the fluorescence quantum yield, fluorescence lifetime, radiative (kr) and non-radiative (knr) rate constant values. It was observed that the fluorescence quantum yield values decreased linearly with increasing solvent polarity. This study proved the new dyes including isopropyl methanesulfonate group displayed different behavior from previous studies of aminophthalimide derivatives in water. It was recommended that these new dyes having interesting properties by changing solvent can be used various applications such as environmentally sensitive fluorescent probes, labels in biology, laser industry. © 2017, Springer Science+Business Media New York.
PubMed ID: 28078631
Keywords: Aminophthalimide; Solvatochromic; Solvent-solute interaction; Stokes shift